Physicochemical Properties and Optimization of Pigeon Peas (Cajanus cajan) Yogurt: Influence of Starter Culture and Incubation Techniques - Munir, Nur Faidah; Harianti, Indah; Dwiyanti Mustaka, Zulfitriany; Rahmaniar; Mariani; Matti, Agussalim; Kadir, Muhammad (International journal of technology and education research, 2025)
Pigeon peas(Cajanus cajan (L.)) are a type of legume with potential for development as a sustainable alternative source of plant-based protein. These beans have a relatively high protein content, approximately 27–28%. This study aims to analyze the effects of variations in lactic acid bacteria cultures and incubation methods on the production of yogurt made from local Pigeon peas beans. The study employed a Completely Randomized Design (CRD) to test variations in Lactic Acid Bacteria (LAB) cultures (comprising Greek yogurt culture and powdered culture) combined with three different incubation methods: incubation at room temperature, in a thermos, and in a modified incubator. Data were analyzed using a two-way Anova. The results showed that variations in LAB cultures had a significant effect on protein content, moisture content, fat content, viscosity, and pH. Meanwhile, the incubation method had a significant effect on protein content, moisture content, ash content, total lactic acid, fat content, viscosity, and pH. The best Pigeon peas bean yogurt was obtained from the powdered culture treatment using the incubation method with a modified incubator, yielding a protein content of 3.47%; ash content of 0.69%; total lactic acid of 0.66%; fat content of 1%; viscosity of 0.47 cP; pH of 3.82; and moisture content of 83.19%. The results of the organoleptic test showed that the criteria for color, aroma, and taste were met, while on average, the panelists strongly liked the texture of the yogurt.